A multi-sectoral approach to the Harrod foreign trade multiplier - Andrew B. Trigg; Ricardo Azevedo Araujo (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2018)
With this inquiry, we seek to develop a multi-sectoral version of the static Harrod foreign trade multiplier, by showing that it can be derived from an extended version of the Pasinettian model of structural change and international trade. This new version highlights the connections between the balance of payments and levels of employment and production. It is also shown that from this disaggregated version of the Harrod foreign trade multiplier we can derive an aggregate version of the multiplier. By following this approach we go a step further in establishing the connections between the structural economic dynamic and the balance-of-payments-constrained-growth approaches.
Keywords: O19; F12; 330; structural economic dynamics; foreign trade multiplier; balance-of-payments-constrained growth